Green entrepreneurial farming: A dream or reality?. (20th May 2019) - Sher, Ali; Mazhar, Saman; Zulfiqar, Farhad; Wang, Dong; Li, Xiangmei
Abstract: Like other developing countries, Pakistan is under severe economic pressure and striving to boost entrepreneurial orientation for achieving growth through minimal depletion of natural resources. In order to facilitate widespread and successful adoption of green entrepreneurial farming, it is crucial to address barriers inhibiting the uptake of green entrepreneurial activities in farming for the sustainability of natural resources as well as food provision. To this end, the present study aimed to investigate barriers in the adoption of green entrepreneurial farming in Pakistan. To fulfill the study objectives, after a comprehensive literature review and field visit, 34 barriers were identified. The results based on ranking analysis identified 20 out of 34 barriers as critical barriers to adoption of green entrepreneurial farming in the country. Furthermore, factor analysis was employed to group underlying 20 critical barriers into six major categories viz. 1) training and development-related barriers, 2) entrepreneurial orientation-related barriers, 3) market orientation-related barriers, 4) customer orientation-related barriers, 5) innovation orientation-related barriers, and 6) green supporting supplies-related barriers. Results showed that most dominant barrier among six groupings was training and development-related barriers and the marginal role of government in the provision of such endeavours. This implies that government needs to play a more active role in the adoption and promotion of green entrepreneurial farming in Punjab, Pakistan.